Anticipatory anxiety about future dementia‐related care needs: towards a dementia‐friendly community. Issue 6 (18th March 2019) - Okamura, Tsuyoshi; Sugiyama, Mika; Inagaki, Hiroki; Murayama, Hiroshi; Ura, Chiaki; Miyamae, Fumiko; Edahiro, Ayako; Motokawa, Keiko; Awata, Shuich
Abstract : Aim: Although a dementia‐friendly community is a global goal, community‐dwelling persons with dementia continue to have unmet care needs. The aim of this study was to explore the characteristics of persons who experience anxiety about the possibility of not receiving proper dementia care should they need it in the future. Methods: A questionnaire was mailed to all residents aged 65 years or older ( n = 132 005) living in one Tokyo district. The questionnaire included an item that measured anxiety about the possibility of not receiving proper dementia care as well as items about sociodemographic variables, depressive symptoms, frailty, housebound status, socioeconomic status, social support, access to a general practitioner (GP), and experience of dementia care. Results: Of the 74 171 participants who responded to the anxiety item, 58 481 (78.8%) reported anxiety about the possibility of not receiving proper dementia care should they need it in the future. Simultaneous multiple logistic regression analysis indicated that factors associated with this anticipatory anxiety were depressive symptoms, frailty or prefrailty, being female, not being currently socioeconomically disadvantaged, not having someone who can take you to the hospital when you do not feel well, being younger (65–74 years), being married, not trusting in neighbours, higher educational level (>9 years), not having someone to consult when you are in trouble, not working, having been socioeconomically disadvantaged in childhood, only greeting or less with neighbours, and not having the experience of dementia care. Having access to a GP, living alone, and going out less than once a week did not show a significant association. Conclusions: This large‐scale study explored factors associated with anticipatory anxiety about the possibility of not receiving proper dementia care should it be needed in the future. Further studies concerning interventions to decrease such anxiety are needed.